2013
DOI: 10.1111/head.12251
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Health‐Related Disability in Children With Migraine

Abstract: Although migraine was a cause of school absenteeism, most of the children with migraine showed little or no disability regarding daily life activities and their quality of life was similar to that of children without headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
2
42
1
Order By: Relevance
“…A survey of young patients (age range: 2‐18 years) who attended a children's headache center reported that migraine affects QoL at levels equivalent to or greater than other chronic illnesses of childhood, particularly with respect to school performance and emotional functioning . A separate study found that children with migraine were absent from school activities, did not perform household tasks, and did not participate in leisure activities for 23.9 days, on average, during the last 3 months because of migraine . Notably, children self‐reported a worse emotional QoL but not HRQoL, whereas the parents perceived their general, emotional, and HRQoL to be worse …”
Section: Burden Of Diseasementioning
confidence: 99%
“…A survey of young patients (age range: 2‐18 years) who attended a children's headache center reported that migraine affects QoL at levels equivalent to or greater than other chronic illnesses of childhood, particularly with respect to school performance and emotional functioning . A separate study found that children with migraine were absent from school activities, did not perform household tasks, and did not participate in leisure activities for 23.9 days, on average, during the last 3 months because of migraine . Notably, children self‐reported a worse emotional QoL but not HRQoL, whereas the parents perceived their general, emotional, and HRQoL to be worse …”
Section: Burden Of Diseasementioning
confidence: 99%
“…1, 2 Tension-type headache (TTH) is the most common with prevalence rates ranging from 10 to 25 percent in school-aged children. 3 Migraine headaches are somewhat less common with prevalence ranging from about 3 percent in younger school-aged children to nearly 20 percent in older adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although previous publications have discussed the management of pediatric migraine in the emergency department (ED), [4][5][6] there is only a single pediatric controlled trial conducted in the ED setting 7 ; therefore, most of the recommendations are based on treatment trials in adults or other non-ED settings with off-label use of medications.…”
mentioning
confidence: 99%